The Role of Community Assessments, Place, and the Great Recession in the Migration Intentions of Rural Americans1. (9th July 2013) - Ulrich‐Schad, Jessica D.; Henly, Megan; Safford, Thomas G.
Abstract: Many rural areas of the United States are experiencing population decline due to out‐migration. However, others—especially those places rich in natural amenities and recreational opportunities—are attracting new residents and losing less of their native population. In this article we investigate the predictors of rural Americans' migration intentions by examining how individual‐level community assessments, including community attachment and perceptions of community‐level problems, shape rural Americans' migration decision making while controlling for individual and place effects. Drawing on survey data from 17, 000 residents in 11 different rural areas around the United States, we find that community attachment is a key predictor of rural migration, even during periods of economic recession, and regardless of individual and place characteristics or perceptions of community‐level problems. We also find that multiple dimensions of community attachment (e.g., practical, natural, family, community trust) have independent effects on the propensity of rural residents to migrate. Our research contributes to knowledge on migration trends among rural Americans by exploring the complicated reasoning behind why people stay in, or move to, certain rural communities and not others.